Polish Independent Press Review, no. 9 (1987) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). Profiles of Major Independent Polish Publications: "CDN - Głos Wolnego Robotnika" / by Michał KołodziejThe Polish Independent Press Review continues its series on leading independent periodicals with a look at CDN - Głos Wolnego Robotnika, which is published each week in Warsaw by the Interfactory Workers' Committee of Solidarity. The Independent Press on US Visitors to Poland / by Michał KołodziejThe numerous recent visits of American diplomats to Poland were commented upon in the independent press. It devoted most attention to their contacts with Solidarity leaders and representatives of the democratic opposition. Brutality and Harassment by the Authorities Continue / by Nika KrzeczunowiczDespite the prevailing opinion about "normalization" in Poland, brutality and the harassment of peaceful citizens by the police continue, as documented by the independent press.